Pembuatan Media Pembelajaran PAUD Berbasis Bahan Alam Di TK Alifia Samarinda - Andi Aslindah; Lilis Suryani (Jurnal Pengabdian Ahmad Yani, 2021)
Learning media is a component that contributes to the implementation of the learning process at the education unit level. The role of the media in learning, especially in early childhood education (PAUD) is very important, considering the development of children at that time was in a period of concrete thinking. However, there are still teachers who think that the role of the media in the learning process is only as a tool and may be ignored when the media is not available in schools. Even though the learning media used in the early childhood learning process should not be obtained from the store by buying. However, teachers and parents can create their own media. One solution that can overcome this condition is that it is necessary to conduct a training in making creative, attractive and easily available media in a nature-based environment. The community service activities carried out in the form of socialization and training in making learning media based on natural materials provide benefits for training participants, including: 1) For Teachers: Adding insight and increasing teacher creativity in preparing learning media by utilizing natural materials-based materials. 2) For Parents: Gained insight and experience to be more creative and innovative in assisting children to be creative in making a work (learning media) by utilizing materials that can be obtained from the natural surroundings. 3) For Children (students): Increase their self-confidence to be more skilled in performing work in creating a work (media) by collaborating with their respective parents/guardians. Keywords: PAUD Learning Media, Natural Materials